2023
DOI: 10.3390/nu15041058
|View full text |Cite
|
Sign up to set email alerts
|

The Ketogenic Diet in Children with Epilepsy: A Focus on Parental Stress and Family Compliance

Abstract: (1) Background: The aim of our study was to evaluate parental stress after 6 and 12 months of a ketogenic diet, considering demographic and clinical variables (epilepsy type, epilepsy duration, seizure number, antiseizure medications, comorbidities, efficacy, and adverse events). (2) Methods: We consecutively enrolled 36 children aged between 3 and 10 years who had been diagnosed with various types of drug-resistant epilepsy and who were in therapy with a ketogenic diet for better seizure control. A standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…Evidence also demonstrated some efficacy in improving cognitive abilities ( Rho and Boison, 2022 ; Zhu et al, 2022 ). However, such dietary therapy is difficult to adhere to, needs continuous monitoring, is unsuitable for all patients, and has several side effects ( Rho and Boison, 2022 ; Zhu et al, 2022 ; Operto et al, 2023 ). A better understanding of the molecular mechanisms through which KD and novel ASM can alleviate seizures and cognitive deficits is fundamental for developing new drugs with an overall efficacy while avoiding side effects as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also demonstrated some efficacy in improving cognitive abilities ( Rho and Boison, 2022 ; Zhu et al, 2022 ). However, such dietary therapy is difficult to adhere to, needs continuous monitoring, is unsuitable for all patients, and has several side effects ( Rho and Boison, 2022 ; Zhu et al, 2022 ; Operto et al, 2023 ). A better understanding of the molecular mechanisms through which KD and novel ASM can alleviate seizures and cognitive deficits is fundamental for developing new drugs with an overall efficacy while avoiding side effects as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…These feeds have been developed for children following a KD to provide variety and convenience, support adherence, and to help ensure nutritional needs are met. However, before now, there were no nutritionally complete feeds available which were suitable for older children, adolescents, and adults, despite the increasing use of KDs to manage drug‐resistant epilepsy in these groups 14,15 . There is also a growing interest in MCTs, particularly octanoic (C8) and decanoic (C10) acids into medical feeds for drug‐resistance epilepsy due to an increasing evidence of their antiseizure effects 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, before now, there were no nutritionally complete feeds available which were suitable for older children, adolescents, and adults, despite the increasing use of KDs to manage drug‐resistant epilepsy in these groups. 14 , 15 There is also a growing interest in MCTs, particularly octanoic (C8) and decanoic (C10) acids into medical feeds for drug‐resistance epilepsy due to an increasing evidence of their antiseizure effects. 16 Consequently, a ready‐to‐use, 2.5:1 ratio, nutritionally complete liquid feed including MCTs (25.6% of total fat) has been developed, suitable for children from 8+ years, adolescents and adults as a sole source of nutrition or as a supplementary feed, and can be used as part of any of the variant forms of the KD.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term adherence to treatment with KDTs is often difficult for the patient and caregivers [5,[15][16][17][18][19][20][21]. The results of a meta-analysis including 11 studies with KDTs in adults revealed combined compliance rates of 45%, 38%, and 56% for all types of KDTs, CKD, and an MAD, respectively [22].…”
Section: Introductionmentioning
confidence: 99%